3. Audio example: Air pour le Panharmonicon - Cherubini, Luigi, 1760–1842 (composer):::Creator::::::::::::; Guttierez, Andrea (transcriber):::Contributor:::::::::::: (2022)
Cherubini's Air pour le Panharmonicon was composed specifically for the Panharmonicon to play, as was Beethoven's Wellingtons Sieg. Almost nothing is known about the circumstances surrounding its composition, but the manuscript score (now preserved in the Berlin State Library) is inscribed "Paris, 1806." Maelzel presumably approached Cherubini with the commission while he was in Paris demonstrating his musical inventions and mechanical chess-player. The Air pour le Panharmonicon is a songlike composition in 3/4 meter that showed off the capabilities of the instrument's mechanical wind ensemble. Cherubini's score divides the instruments into two sections: a main section titled "Cantabile" (a musical term meaning "in a singing style") and a smaller section called "Echo." The Cantabile instruments introduces the main melody, which is then repeated in a decorated form that includes "echo" effects. A contrasting middle section turns to the minor key and introduces the trumpets and horns, and finally the main theme returns with yet more echoes and melodic decorations.